Effectiveness of Natural Zeolite Mass Variation for Turmeric Solution Adsorption Process - Naufal Ahmad Daffa (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
The purpose of this study was to observe the effectiveness of adsorption process in turmeric solution with different zeolite masses. The method used was to highlight the solution with flashlight which was then measured using a lux meter. To support this research, we used a solution of turmeric with zeolite with mass variations ranging from and tested 3 times with a lux meter. The results obtained indicated that there are differences in the adsorption rate of turmeric solution with zeolite mass from 1 to 2,5 grams. This difference occurred because of the difference in the mass of the zeolite between which adsorbed the turmeric solution. The lux meter showed different results in each test and the water clarity level was different for each added mass variation. In addition, the compatibility of the experimental results with the isotherm adsorption model shows the adsorption mechanism that occurred. Thus, the difference in mass has an impact on use on a larger scale as needed. This research is expected to provide new knowledge for the community about the benefits of zeolite for water purification process in daily life.